Characteristics of cardiac regulation of tennis players with physical impairments in competition - V. V. Kalsina; A. N. Nalobina (National Electronic Information Consortium (NEICON), 2020)
Objective: to define the characteristics of the regulation of the cardiac activity of table tennis athletes with physical impairments in conditions of competitive stress. Materials and methods: the analysis of heart rate variability. Study included 44 table tennis athletes with physical impairments, mean age 28,1±2,3 years. Sports qualification of participants: from the III sports category up to the master of sports. Results: vegetative regulation of cardiac activity was characterized by activation of the central contour of regulation. It was associated with a higher level of fitness of the cardiovascular system. Athletes of low qualification had inadequate reaction of the cardiovascular system on the competitive stress. It involved the strengthening of the autonomous regulation loop before the competition. Conclusions: the revealed signs of overfatigue and under-recovery in tennis players of low level of sports qualification testified to the necessity of using recovery means for this category of athletes in the training process.